Survival rate and growth patterns in Festuca dolichophylla under similar conditions - Paucar, Y. (2023)
The aim of this study was to evaluate the survival rate and growth patterns in five populations of Festuca dolichophylla under similar conditions. Five accessions were obtained from each population: Comunidad Campesina Pastales Huando – Huancavelica (CCPH), Lachocc South American Camelid Research and Development Center of the National University of Huancavelica (CIDCSL), as well as from the regions of Junín, Pasco and Puno. Each accession was divided into six plants and installed in a uniform CCPH soil. After 12 months of establishment, the survival rate and monthly morphological characteristics during growth were estimated. Survival rates were from 43.3% in CIDCSL plants up to 96.7% in Puno plants (p<0.05) and with high variability within each population. Plant height, growth rate, number of stems, stem appearance rate and number of leaves also showed high variability and differences between populations, except for the rate of leaf appearance. The variability and differences found would be due to the different genetic constitution of each population since the environment was similar. On the other hand, an orderly growth pattern of the plant was observed, where it first grows, then increases the number of stems and finally the number of leaves.